"Know Whence you Came": Psychoanalytic Theory, Queer Theory, and the Mixed-Race Experience. Issue 1 (2nd January 2019) - Jamali, Alexandra P.; Méndez, Teresa
Abstract: Deeply rooted U.S. cultural practices and legislative processes have facilitated the dissociation, erasure, and evasion of engagement with mixed-race subjectivities. As multiracial clinicians, we attempt to reexamine the discourse around race in psychoanalytic literature, questioning the process by which dominant monoracial norms have been constructed, reproduced, and codified as normal and acceptable. We propose that the absence of multiracial subjectivities from the psychoanalytic literature reflects a broader social discomfort with and cultural dissociation of the mixed-race experience. We further suggest that it is necessary to engage both analytically and queer-ly with the subjective experience of racial multiplicity—positing that multiracial subjectivities might best be understood as subjectivities that are "racially queer."